Child care participation among Indigenous children in Canada - Findlay, Leanne; Arim, Rubab; Frank, Kristyn; Melvin, Alexandria; Bleakney, Amanda; Kumar, Mohan (Western University, 2023)
The release of a Canadian Indigenous Early Learning and Child Care Framework highlights the importance of recent, Indigenous-specific information to describe the landscape of child care among Indigenous children in Canada; however, there has been a gap in identity-specific, national data on child care for Indigenous children. The purpose of the current study was to address data gaps on participation in child care for First Nations children living off reserve, Métis, and Inuit children. Furthermore, two years of data are examined which provide information on child care use both prior to and during the first year of the COVID-19 pandemic. In 2019, First Nations children living off reserve (49%) and Inuit children (42E %)1 were significantly less likely to participate in child care compared with non-Indigenous children (60%), although Métis children (60%) were equally likely to participate in child care compared with non-Indigenous children. Only First Nations children living off reserve (40%) were significantly less likely than non-Indigenous children (53%) to participate in child care in 2020. In terms of the type of child care used, Inuit children were more likely to be in a daycare centre (70%) compared with non-Indigenous children (52%) in 2019, although Inuit children’s participation in a daycare centre dropped to 46E% in 2020. This is likely due to public health restrictions which closed many child care centres during the pandemic, as over one-third of child care in the territories is centre-based. The findings provide important information about patterns of child care use for Indigenous children both before and during the pandemic.